2017
DOI: 10.1097/pas.0000000000000754
|View full text |Cite
|
Sign up to set email alerts
|

The Microcystic, Elongated, and Fragmented (MELF) Pattern of Invasion

Abstract: MELF invasion has been associated with non-vaginal recurrences and lymph node (LN) metastases in multi-institutional case control studies, but has not been well examined in large single institution cohorts. Hysterectomy specimens with FIGO 1 endometrioid endometrial carcinoma (EEC) and lymphadenectomies from 2007 to 2012 were identified. Electronic medical records and histologic slides were reviewed. Of 464 identified cases, 163 (35.1%) were noninvasive, 60 (12.9%) had MELF, 222 (47.8%) had a component of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 25 publications
3
25
0
Order By: Relevance
“…This pattern of myoinvasion shows immunohistochemical features in tumor cells suggesting that the phenotypic changes are related to the phenomenon of “epithelial-mesenchymal transition” 30,90. A MELF pattern of invasion is reported to be associated with a higher likelihood of nodal involvement and distant recurrence but its significance as an independent risk factor remains unclear 91,92, possibly partly related to a level of subjectivity in its recognition.…”
Section: Pathologic Prognostic Factorsmentioning
confidence: 96%
“…This pattern of myoinvasion shows immunohistochemical features in tumor cells suggesting that the phenotypic changes are related to the phenomenon of “epithelial-mesenchymal transition” 30,90. A MELF pattern of invasion is reported to be associated with a higher likelihood of nodal involvement and distant recurrence but its significance as an independent risk factor remains unclear 91,92, possibly partly related to a level of subjectivity in its recognition.…”
Section: Pathologic Prognostic Factorsmentioning
confidence: 96%
“…To describe an unusual type of this invasion, Murra et al introduced the acronym “MELF” for microcystic, elongated and fragmentated pattern of myometrial invasion in endometrioid ECs, but they failed to demonstrate a statistically significant effect of MELF on overall survival – only a subgroup of women showing a fibromyxoid stromal reaction and MELF had improved survival [ 6 ]. Further studies have revealed that the incidence of MELF in ECs is between 13% and 36% and have shown that its presence is significantly associated with tumor size, lymph node involvement, advanced International Federation of Gynecology and Obstetrics (FIGO) stage, lympho-vascular space involvement (LVSI+), mucinosus differentiation, and papillary architecture [ 7 10 ]. In contrast to the findings reported by Murray et al and Kihara et al, who did not demonstrate any association between MELF and disease-free or overall survivals, Zinkov et al observed a significantly lower survival rate in patients with endometrioid ECs with a MELF pattern compared with MELF-negative women [ 6 , 7 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The DNA fragmentation factor (DFF) complex is localized to the cell nucleus and exists as a dimer comprising DFF40 (caspase-activated DNase; CAD) and DFF45 (inhibitor of caspase-activated DNase; ICAD) [ 17 ]. DFF45 is cleaved by caspase-9 at the end of the apoptotic cascade, which results in the release of DFF40 from the DFF40/DFF45 complex, leading to DFF40-mediated DNA fragmentation (DNA laddering) [ 10 ]. However, DFF45 is not merely an inhibitor of DFF40, as its presence is also required for the proper folding of DFF40, which is necessary for production of the active protein [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, these data cannot be directly extrapolated to our series because these authors used a different classification system to the one described in 2013, which is now widely accepted [8]. Moreover, they have few cases within the infiltrative category, in contrast to what is widely described [9][10][11][12]. In our study, we found an association between the presence of the infiltrative glands pattern and the DFS of the patients.…”
Section: Discussionmentioning
confidence: 52%
“…Since the proper recognition of five patterns of EEC myoinvasion [8], much attention has been paid to the microcystic, elongated and fragmented glands (MELF) pattern of myoinvasion. The MELF pattern has been associated with an increased risk of lymph node metastases, but without any impact on prognosis [9,10]. In contrast, there is little published data regarding the risk of recurrence associated with any of the other patterns [11,12].…”
Section: Introductionmentioning
confidence: 99%